Experience of Surgical Management of Chylothorax Over a Period of 10 Years - Muhammad Imran, Anila Basit, Asif Ahmed, Abdullah Wahaj, Abdul Baseer (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Chylothorax is a rare but significant condition characterized by the accumulation of chyle in the pleural space. It can result from various etiologies, including trauma, malignancies, infections, and congenital defects. While conservative treatments are often used, surgical intervention may be required in refractory cases. This study aimed to evaluate the long-term outcomes of surgical management of chylothorax over a 10-year period at our institution. Methods: This retrospective study was conducted at Lady Reading Hospital, Peshawar, KPK Pakistan during March 2011 to March 2021. Data included 550 patients diagnosed with chylothorax. Data on patient demographics, etiology, surgical interventions, postoperative complications, length of hospital stay, recurrence rates, and follow-up outcomes were collected. Surgical interventions included thoracic duct ligation, pleurodesis, pleurectomy, and video-assisted thoracoscopic surgery (VATS). Statistical analyses were performed to assess the success rates and complications associated with each surgical approach. Results: The overall resolution rate of chylothorax was 85%. Thoracic duct ligation had the highest success rate (90%), followed by pleurectomy (78.2%), pleurodesis (72.2%), and VATS (84%). Postoperative complications occurred in 15.5% of patients, with infection (6.4%) and prolonged air leak (5.1%) being the most common. The mean length of hospital stay was shortest for VATS (6.5 days), followed by thoracic duct ligation (7.8 days), pleurodesis (10.5 days), and pleurectomy (11.2 days). The recurrence rate of chylothorax was 7.5%, with higher rates observed in pleurodesis (12.2%) and pleurectomy (9.1%). Conclusions: Surgical management of chylothorax is generally effective, with thoracic duct ligation being the most successful intervention. Although postoperative complications are common, they are generally manageable. Keywords: Chylothorax, surgical interventions, postoperative complications, thoracoscopic surgery.